A comprehensive, population level evaluation of previously reported drug triggers of pemphigus highlights immunomodulatory capacity as a common characteristic - Baroukhian, Justin; Seiffert-Sinha, Kristina; Sinha, Animesh A. (Frontiers in Immunology, 2025)
QuestionCan previously reported, largely anecdotal associations between exposure to any of a comprehensive list of putative trigger drugs and the development of pemphigus be reproduced using population level data?FindingsIn this series of observational, retrospective, case-control, pharmacovigilance analyses of the FDA Adverse Event Reporting System, the odds of reporting the adverse event pemphigus were significantly elevated among individuals exposed to 11/36 previously reported trigger drugs namely, gold sodium thiomalate, penicillamine, piroxicam, rifampin, hydroxychloroquine, imiquimod, hydrochlorothiazide, irbesartan, lisinopril, nivolumab, and nifedipine.MeaningEnvironmental exposures such as drugs are relevant players in the pathogenesis of autoimmune diseases and clinicians who treat patients with autoimmune blistering diseases such as pemphigus should consider performing a detailed medication history leveraging this information regarding deleterious drug-disease interactions at initial evaluation as well as longitudinal monitoring of patients to better inform clinical care decisions.ImportancePemphigus vulgaris (PV) is a rare, potentially fatal autoimmune disease with pathogenic contributions from both genetic as well as environmental factors, notably drug exposures. Despite anecdotal reports linking multiple drugs to PV, corroborating evidence from large datasets is missing.ObjectiveTo examine the extent to which previously reported associations between a comprehensive list of 36 drugs implicated in PV pathogenesis could be replicated using population-level pharmacovigilance data.DesignSeries of observational, retrospective, case-control, pharmacovigilance analyses (one analysis/drug, 36 total).SettingPopulation based.ParticipantsIndividuals who submitted a report of a drug-related adverse event to the FDA from Q4 of 2003 to Q2 of 2023.ExposureCases were identified by the presence of adverse events described by the MedDRA preferred term “pemphigus” (10034280) and then sorted based on exposure to each of the drugs of interest.Main outcomes and measuresReporting Odds Ratios (RORs) quantifying the association between a given drug exposure and reports of pemphigus adverse events.ResultsThe analyses revealed statistically significant associations between reports of pemphigus and exposure to 11/36 previously reported drugs, two of which had particularly high RORs (>200) [gold sodium thiomalate (ROR, 266.0; 95% CI, 202.6-349.3) and hydroxychloroquine (ROR, 282.6; 95% CI, 261.0-306.1)], three had very strong RORs (14-45) [penicillamine (ROR, 30.5; 95% CI, 11.4-81.7), piroxicam (ROR, 14.8; 95% CI, 8.2-26.7), and imiquimod (ROR, 42.3; 95% CI, 26.2-68.3)], and six had modestly strong RORs (2-5) [rifampin (ROR, 2.8; 95% CI, 1.4-5.6), hydrochlorothiazide (ROR, 1.6; 95% CI, 1.2-2.1), irbesartan (ROR, 2.7; 95% CI, 1.6-4.4), lisinopril (ROR, 5.3; 95% CI, 4.5-6.2), nivolumab (ROR, 2.7; 95% CI, 1.8-4.1), and nifedipine (ROR, 3.0; 95% CI, 1.9-5.0)]. Associations for other previously reported drugs (25/36) were not detected.Conclusions and relevanceThis study represents a comprehensive evaluation of suspected drug triggers of pemphigus using real-world data. The significant associations reported here provide empirical support for the hypothesis that certain drugs act as triggers for PV. Moreover, all of the drugs found to be associated with PV in this study harbor immunomodulatory capacity, suggesting that the ability to induce such perturbations, directly or indirectly, may be a critical factor connecting drug exposure to pemphigus pathogenesis. However, the absence of signals for other previously reported putative trigger drugs does not preclude their potential role in PV pathogenesis. Our findings reinforce the need for larger, more definitive studies to confirm these associations and to explore the mechanisms by which these drugs may contribute to PV development. Finally, these findings underscore the importance of considering environmental factors in the development and course of PV in genetically susceptible individuals.